Quantitative Submicron Particulate Characterization by Dark-Field Microscopy. (17th February 2018) - Bernat, T.; Castro, C.; Pasternak, A.; Sin, J.; Stein, O.; Petta, N.
Abstract: The University of Rochester Laboratory for Laser Energetics Laser Direct-Drive 100-Gbar Campaign requires fuel capsules with specified limits on the number of localized surface defects in the 0.1- to 1-µm range. Schafer Livermore Laboratory has applied techniques of bright-field conventional imaging and charge-coupled-device–based dark-field microscopy as a possible method of characterizing the number and sizes of local particle-like defects on these capsules. Through simple experiments, we are able to correlate measured localized light-scattering levels with sizes of spherical polystyrene test particles. We have developed an engineering concept for whole-surface capsule scans based on quantitative dark-field microscopy as well as conventional imaging microscopy. This system and technique will be particularly useful during capsule development and capsule handling (transport, assembly, etc.) investigations.